Psychometric Properties of the Turkish Form of the Social Impact of Sporting Activities Scale - Otkan, Can Cavin; Igdir, Emre Can (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
This study aimed to introduce the Social Impact Scale of Sporting Events to the Turkish literature. The psychometric properties of the Social Impact of Sporting Events Scale were evaluated, and the validity and reliability of the scale in Turkish culture were tested. In order to ensure the correct applicability of the original scale, which consists of 6 factors and 20 items and is rated on a 7-point Likert scale, translation, synthesis, back translation, pre-test, and expert evaluation stages were carried out. For the scale’s construct validity in Turkish culture, exploratory factor analysis (EFA) was tested with 347 participants, followed by confirmatory factor analysis (CFA) with a second study group of 209 participants. Within the scope of reliability analyses, Cronbach’s alpha coefficient was calculated, and total test correlations of the items were examined. The findings showed that the scale had high internal consistency, and the items reliably measured the construct to be measured. As a result, the Social Impact of Sporting Events Scale was revealed to be consistent with the original scale and can be used as a valid and reliable measurement tool in Turkish culture.